Awareness and practice of patients with Helicobacter pylori infection toward their disease in the Riyadh Region, Saudi Arabia - Huda H Abdelrahman; Sarah M Alotaibi; Sobhia N Abanmi; Hessah A Alosaylan; Amal K Almutairi; Nourah H Almutairi; Shahad N Alrashidi; Abeer T Almutairi (Journal of Pharmacy and Bioallied Sciences, 2024)
Objective: This study aimed to study the awareness and practice of patients with Helicobacter pylori (H. pylori) toward their disease in the Riyadh region, Saudi Arabia. Material and Methods: This is a descriptive cross-sectional community-based study, in the central region of the kingdom. The target population of this study was adult patients with H. pylori infection, and a sample of 808 Saudi and non-Saudi male and female individuals were randomly selected using an online questionnaire. A consent form was obtained from all participants. Ethical approval was obtained from the university ethics committee. Results: There were a total of 808 responses. Most participants were female (89.4%) (n = 722) and between the ages of 35 and 60 years (60.8%), and most participants had a bachelor's degree (62.4%). 53.47% of the participants have good knowledge regarding their disease. Most of the participants knew it could cause gastric and duodenal ulcers (82.5%), but they did not know the infection might cause gastric cancer (48.6%). Conclusion: The study concluded that the majority of patients with H. pylori infection (53.47%) have good knowledge regarding their disease. Additionally, many participants were aware of the symptoms associated with H. pylori. Furthermore, many participants complained about their treatment.